Ochrobactrum anthropi Keratitis in a Boston Type 1 Keratoprosthesis Recipient. Issue 5 (May 2021) - Ma, Kevin K.; Tone, Stephan Ong; Chodosh, James; Saeed, Hajirah N.
Abstract : Purpose: To report a case of Ochrobactrum anthropi keratitis in an eye with a Boston type 1 keratoprosthesis. Methods: This is a case report and review of the literature. Results: A 78-year-old man with a history of implantation of a Boston type 1 keratoprosthesis in the left eye presented for a routine follow-up with no acute complaints. In the left eye, visual acuity was 20/60 and slit-lamp examination revealed a 1.5-mm inferotemporal corneal infiltrate adjacent to the optic stem. Corneal cultures grew abundant O. anthropi . After 7 weeks of topical antimicrobial therapy and placement of a temporary tarsorrhaphy, the keratitis resolved. Conclusions: Ochrobactrum anthropi is an organism associated with indwelling medical devices and can be pathogenic in eyes with implanted keratoprostheses.